The Silence of the Lambdas: Deterring Incapacitation Research - Miles, Thomas J. (Journal of quantitative criminology, 2007)
This essay provides an economist’s perspective on criminological research into incapacitation effects on crime. Our central argument is that criminologists would do well to substantially scale back the enterprise of trying to estimate the various behavioral parameters central to a micro-level approach to measuring incapacitation effects, including the annual rate of offending outside of prison (λ) and the lengths of criminal careers. One problem with this line of research is practical: for example, mean estimates of self-reported criminal activity by incarcerated prisoners are quite sensitive to reports by the most criminally active offenders. But the larger concern is conceptual—the incapacitation effects from a given change in sentencing policy may be undermined by the possibility of replacement effects, and at the same time omit other benefits that may arise from deterrent effects on crime. A more promising approach is to identify plausibly exogenous changes in sentencing policy in order to estimate the net impact on crime from the combined effects of incapacitation, deterrence and replacement.